Vitamin D and fractures: a sistematic review - L. Idolazzi (Reumatismo, 2011)
Vitamin D deficiency is a relevant problem particularly in south Europe and in over 65 year old subjects, that is often underestimated. Vitamin D deficiency represents a real medical emergency also for its role in the patho-physiology of muscular-skeletal diseases. Chronic vitamin D deficiency leads to severe bone and muscular outcomes including: osteoporosis, osteomalacia and proximal limb myopathy. These increase the risk of falling and fractures. The efficacy of vitamin D treatment in decreasing the fracture risk has been reporting in several studies. The negative results of some recent studies questioned the clinical vitamin D efficacy. However these studies have a number of methodological problems and even the interpretation of the results is questionable. In this paper we review all these aspects. This analysis permits to confirm that vitamin D treatment can be extremely cost-effective when given to people at high risk of deficiency. An acceptable compliance is obviously of critical importance.